Comparison of cultural values in the myths of Mount Semeru and Mount Kunlun - Alexandra, Angie; Budianto, Pauw (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2024)
Myths are stories about gods and goddesses who are connected with supernatural powers, used by ancestors as instruments to interpret phenomena that could not be explained. The existence of myths functions as an educational tool to instill specific cultural values and beliefs. This exploration is directed at comparing the myths of Mount Semeru and Mount Kunlun to gain further enlightenment regarding the cultural values in the two stories. The research was managed using a comparative descriptive research method through a literature study as a data collection technique. Research has found that the cultural values that are common among the people are that mountains are believed to be the house of gods and other creatures, the peaks of both mountains are trusted to be places where humans cannot pass, and several gods and goddesses are said to have helpers in the form of animals. The differences in cultural values accepted by society are in the form of differences in figures that are prioritized in their distribution and what is prioritized in their transmission in myths. That way, it is known that each region and country still has unique characteristics and specialties in its cultural life, which are reflected in mythical stories.